Pendidikan Islam dan Indeks Pembangunan Manusia (Telaah atas Kontribusi dan Peran Pendidikan Islam dalam Pengembangan IPM) - Muhamad Basyrul Muvid; Miftahuuddin (Al-Ishlah: Jurnal Pendidikan Islam, 2022)
This research focuses on the contribution and role of Islamic education to the process of developing the human development index, with all the problems facing the world of Islamic education. Human development index (HDI) as a process to expand choices for residents in terms of income, health, education, physical environment, and so on. where it needs to be considered in human development are productivity, equity, sustainability, empowerment. The method used in this research is literature study, where the data source is obtained from documents, articles, journals, books and related references. The results of this study are that Islamic education has an important contribution to participate in building superior human resources so that they are able to compete locally, nationally and globally as a representation of efforts to develop a human development index. The role of Islamic education itself as an effort to develop a human development index is needed. The existence of problems in the world of Islamic education can be given the right solution that starts from the structuring of the educational environment, students, educators, teaching materials, evaluations and adequate infrastructure.